Mapping the Falkland Islands Dependencies and British Antarctic Territory, 1956–64 - McHugo, M. Barbara (Polar Record, 1965)
Introduction In May 1956, an article in this Journal described the mapping of the Falkland Islands Dependencies up to that date (Leay, 1956). In March 1962, that part of the Dependencies lying south of 60° S was re-named British Antarctic Territory. This is an account of the maps of both the Dependencies and the Territory that have been published by the Directorate of Overseas Surveys* since 1956 and of the methods that have been used in their production.